ANALISIS PERKEMBANGAN KREDIT MACET PADA PT. BANK MANDIRI (PERSERO) Tbk. UNIT KCP MMU ARGAMAKMUR - -, Ameliana; -, Repuadi (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2014)
Ameliana, Repuadi:An Analysis of Non-Performing Loans Development at Mandiri Bank in Argamakmur.This research used quantitative research. Formulation of the problem in this study is how the development of non-performing loans at PT. Bank Mandiri (Persero) Tbk. Unit MMU KCP Argamakmur. And the methods for collecting data are the documentation and observation. And analysis method used quantitative method. In 2012, the development of non-performing loans begun with an amount 79.000.0000 in June until reached the highest non-performing loans in November, 107.000.000. But this case still can be solved by the customers with installment repayment efforts, so in December 2012, the remaining of non-performing loans has shrinkaged in amount 9000.000. Unfortunately, in January 2013, it rose until 111 millions, but the collection efforts and approaches to the customers are still being done, a result of it, is the non-performing loans fell to 19 millions, although in August rose again to 52 millions. From this case indicated that the condition of Bank is still in good criteria because the NPL?s value is around 0% to 5%.